Plant Regeneration in Amorphophallus muelleri Blume. through Organogenic (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Porang (Amorphophallus muelleri Blume.) usually used to functional food raw materials, caused its high glucomant content. Limitation of conventional propagation both vegetative and generative affected to decreasing of porang production to fulfil market demand. To solve the problem, plant tissue culture technique was chosen to rapid propagate bulbils of porang. So, the aim of this research to determine the combination and concentration of Plant growth Regulators (PGRs), such as 6-Benzylaminopurine (BAP), Naphthaleneacetic Acid (NAA), and Thidiazuron (TDZ) for quality of callus, also growth of callus and shoots for rapid propagation of porang, cause PGRs are one of factors that affect the success of in vitro propagation. Experimental design of this research was completely randomized designed with statistical analysis using analysis of variance (Anova) one way. Difference combination and concentration of cytokinin and auxin as manipulation variables, which several parameters growth of callus, shoots, and roots was observed to indicate the rapid organogenic of porang. The optimal shoot induction medium was Murashige and Skoog (MS) media with 5.0 mg.L-1 BAP and 0.2 mg.L-1 NAA on which number of shoots and shoot height reached 15±1.8 and (7.2±1.86) cm. After shoot formation stage, the proper media for rooting stage was determined, which was Murashige and Skoog (MS) media with 1.0 mg.L-1 NAA resulted the rooting rate reached 100% and roots appear earlier. Optimal combination and concentration of PGRs on micropropagation of Amorphophallus muelleri Blume. from bulbils explant should be known to increase the production of porang, which can fulfil the market demand.